PHONETICS AND INTERACTION IN GERMAN LANGUAGE TEACHING THE ROLE OF METHODS - Babaeva, Vasila (Журнал иностранных языков и лингвистики, 2021)
This article covers a wide range of phonetic errors, phonetic problems and methods encountered in the process of teaching German to students. In addition, phonetic examples and interactive methods and ways to overcome them are illustrated with a few examples.